The impact of ABO blood groups on clinical outcomes and susceptibility to COVID‐19: A retrospective study in an unselected population. Issue 5 (16th March 2021) - Al‐Youha, Sarah A.; Alduaij, Waleed; Al‐Serri, Ahmad; Almazeedi, Sulaiman M.; Al‐Haddad, Mohannad; Jamal, Mohammad H.; Shih, Andrew W.; Al‐Sabah, Salman K.
Abstract: Background: ABO blood groups have been linked to susceptibility to infection with certain microorganisms, including coronaviruses. We examined the relationship between blood group and clinical outcomes in individuals infected with severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) and compared their blood group distribution with the general population. Methods: At the inception of the pandemic, all individuals testing positive for SARS‐CoV‐2 in Kuwait were admitted to one designated coronavirus disease 2019 (COVID‐19) hospital and enrolled in a prospective registry. Patients admitted from February 24 to May 27, 2020, were stratified according to blood group. As a control, blood groups of 3, 730, 027 anonymized individuals representing almost Kuwait's entire population were obtained from a national database. Results: Of 3305 SARS‐CoV‐2–positive patients, 37.1%, 25.5%, 28.9%, and 8.5% were groups O, A, B, and AB, respectively. Univariate analysis revealed no significant differences in severe clinical outcomes or death among the blood groups. However, multivariable analysis demonstrated that group A individuals had higher odds of developing pneumonia compared with non–group A (adjusted odds ratio 1.32, 95% confidence interval 1.02–1.72, p < .036). Compared with the general population, the COVID‐19 cohort had a lower frequency of group O, equivalent frequency of A, and higher frequency of B and AB. No significant difference in the RhD group was found. Conclusion: This study supports potential involvement of the ABO blood group system in predisposing to infection with SARS‐CoV‐2 in an unselected population. Examination of the mechanistic link between blood group and COVID‐19 and its implications on controlling the current pandemic is warranted.